Heat Transfer Measurements on a Rotating Disk - G. Cardone; T. Astarita; G. M. Carlomagno (International Journal of Rotating Machinery, 1997)
Heat transfer to a rotating disk is measured for a wide range of Reynolds number values in the laminar, transitional and turbulent flow regimes. Measurements are performed by making use of the heated-thin-foil technique and by gauging temperature maps with an infrared scanning radiometer. The use of the IR radiometer is advantageous on account of its relatively good spatial resolution and thermal sensitivity and because it allows one to perform measurements down to very low local Reynolds numbers. Data is obtained on three disks, having an external diameter varying from 150mm to 450mm; the smallest disk is used only to measure the adiabatic wall temperature and can rotate up to 21,O00rpm. Heat transfer results are presented in terms of Nusselt and Reynolds numbers based on the local radius and show a substantial agreement with previous experimental and theoretical analyses. Transition to turbulent flow is found at about Re=250,000. A discussion about the role played by the adiabatic wall temperature is also included.